(untitled) (Journal of the College of Basic Education, 2023)
In present study, the logarithm values of comparative halftime log(f t ) for energy levels of Xe 132 isotope yield from decay levels (2.3h(4 + )) of I 32 isotope and (6.427d(2 - )) of Cs 132 isotope gets from study Ref. [5] were calculated, also determined values of spin (J) and parity (  ) for levels that ) by using mathematical equations forming +  , - have transition of Beta (  . with statistical package